Timʻ mrupʻ ne saññʻʹ Kunʻʺ bhoṅʻ khetʻ e khyaṅʻʺ myāʺ - Rheʺ hoṅʻʺ Cā pe Sutesī Ta ūʺ (Ṅve Ya munʻ Cā pe, 1982)
Unpublished poems written during the rule of Konbaung dynasty, 1752-1855 in Burma, transcribed from manuscript.